RECOVERY OF THE TARIMI MANSIONS FROM THE FLOOD OF 2008, TARIM, YEMEN - Jerome, Pamela (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Tarim in Wadi Hadhramaut, Yemen is one of the three main cities in the valley, along with Seyoun, the regional capital, and Shibam, a World Heritage Site. Well known for its iconic 50-m tall mud-brick al-Muhdhar minaret, Tarim is also signiicant for its three important historic cemeteries, manuscript library, and its collection of eclectic mansions dating from the 1870s through the 1930s. On 23-24 October 2008, heavy rains resulted in devastating lash loods that destroyed over 5,000 mud-brick structures in the Hadhramaut Valley. Although only the eastern extremity of Tarim was affected, the mansions, many of which were already in poor condition due to abandonment, suffered greatly from the prolonged downpours. Since their expropriation in the early 1970s by the then-Marxist government of the former People’s Democratic Republic of Yemen, until their return to their rightful owners following the civil war that united north and south, these buildings lacked cyclical maintenance, became “white elephants,” and underwent demolition by neglect. The Tarimi Mansions Preservation Project’s documentation-training program worked from 2000- 08 to record the signiicant abandoned mansions, as well as prepared two feasibility studies for their adaptive reuse. Because of the lood, the Prince Claus Fund for Culture and Development and Yemen’s Social Fund for Development provided emergency funding in 2009-2012 to conserve the exteriors of ten of the mansions, thereby mothballing them until adaptive-reuse functions can be agreed upon with stakeholders. In addition, Tarim was also selected to be the 2010 Islamic Cultural Capital, and simultaneously with our work, the Ministry of Culture restored additional mansion exteriors, so that a total of 17 were preserved. Using the impetus from these events, a Tentative List dossier is also being prepared based on Tarim’s role in the spread of Islam throughout the Indian Ocean.